STUDENT LEARNING SATISFACTION DURING THE COVID-19 PANDEMIC REVIEW OF TEACHER'S PROFESSIONAL COMPETENCY AND LEARNING FACILITIES - Furqon, Mohamad (Jurnal Tunas Pendidikan, 2023)
This study intends to ascertain the impact of learning facilities on student learning satisfaction, the impact of learning environments on student learning satisfaction, and the interaction between teacher professional competency and learning environments. Utilizing a quantitative methodology, this investigation. 114 students in class XII Accounting and Finance made up the study's population, and 80 of those students made up the sample utilizing the proportionate stratified random sampling method. The findings demonstrated that learning facilities and teacher professional competence both had a positive and significant impact on student learning satisfaction, with learning facilities having a positive and significant influence level of 48% and teacher professional competence having a positive and significant influence level of 49%. Having a 60.6% influence on student learning